2007
DOI: 10.1055/s-2007-990305
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Endoscopic Third Ventriculostomy in Obstructive Hydrocephalus

Abstract: This multicentric study reports on 140 patients who underwent endoscopic third ventriculostomy for obstructive hydrocephalus in four Italian neurosurgical centers between 1994 and 1999. Its aim is to define the long-term outcome of these patients many years (6-12) after the initial procedure. The study includes both children and adults; the etiology of the hydrocephalus was malformative aqueductal stenosis in 88 cases (62.8%), compression by tumors of the mesencephalic and pineal regions and posterior fossa in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…In other cases, the hydrocephalus is an acquired condition that develops later in life due to a brain tumor or cyst, head injury, or an infection such as meningitis. In another study Gangemis et al 9 presented 140 patients with obstructive hydrocephalus and have reported that the common etiology of hydrocephalus was acquiductal stenosis in 95 cases and compression by tumour in 45 cases. In present study, the etiology of hydrocephalus is acquiductal stenosis in 31 cases and compression by tumour in 29 cases which is consistent with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the hydrocephalus is an acquired condition that develops later in life due to a brain tumor or cyst, head injury, or an infection such as meningitis. In another study Gangemis et al 9 presented 140 patients with obstructive hydrocephalus and have reported that the common etiology of hydrocephalus was acquiductal stenosis in 95 cases and compression by tumour in 45 cases. In present study, the etiology of hydrocephalus is acquiductal stenosis in 31 cases and compression by tumour in 29 cases which is consistent with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…It also offers the possibility of using ETV for treatment of associated hydrocephalus. 9,11 Ventricular tumors represent a heterogeneous group in terms of histology and therapy and often present with common clinical history and radiological aspects. These lesions can be benign or malignant and may simulate malformative or infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Endoscopic navigation to detect the lesion in patients with small ventricles is also possible using frameless neuronavigation. 1,18,22 Because intra-and paraventricular tumors account for just 2% of all intracranial tumors, studies regarding the effectiveness and safety of endoscopic biopsy have been limited to just a few series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,17,35 The influence of age at the time of ETV on the long-term success should be mentioned. There are reports of low long-term success rates, e.g., 35% and 53%, in patient series comprised exclusively of children younger than 2 years.…”
Section: Fig 3 Influence Of Underlying Pathology On Long-term Etv Smentioning
confidence: 99%